Desain Kemasan Dan Label Produk Enbal Pada UMKM Nen Te Idar Desa Ngilngof, Maluku Tenggara - Tahdeus Maturbongs; Maudy Marla Tanihatu; Saul Ronad Jacob Saleky (Jurnal Administrasi Terapan, 2024)
Indonesia has a variety of cultures, one of which is traditional food. This culture can be a unique capital attraction so it must be maintained and preserved. Nen Te Idar is one of the SME engaged in local food eating traditional south-style Southeast Maluku. Enbal Ngilngof has the advantage of being produced using an unconventional material, namely cassava. However, behind these advantages, this SME still packages its products in a simple way by using traditional packaging methods, namely by using candles as a substitute for a plastic press, besides that the labels used have not fully included product information so that the products are difficult for consumers to remember visually. The purpose of this study is to determine the application of packaging design and enbal product labels to Nen Te Idar. The author uses SWOT and VIEW analysis methods as well as theories about packaging and label designs so that they can create more attractive packaging and label designs, provide visual memory so that products are easier to remember and can increase consumer attractiveness while being a differentiator with competitors with the same product. Based on these results, it can be concluded that a good and attractive packaging and label design can increase attractiveness and interest and reach more consumers and also be a differentiator for competitors in the same field. Keywords : Packaging, Labeling, SME and Products